'Bad Banks' with Chinese Characteristics: an Ongoing Transformation. Issue 133 (2nd January 2022) - Pereša, Irena; Vidon, Edouard
ABSTRACT: This article analyzes the experience of four asset management companies (AMCs) or ʽbad banks' established in China in 1999 to address a systemic build-up of non-performing loans (NPLs). It describes the modalities of NPL transfers across several rounds of government interventions. It explains the AMCs evolving asset structure, funding and operations, with particular focus on a significant change in their business model. Overall, AMCs have helped stabilize the Chinese financial sector, albeit at a substantial fiscal cost. While they became permanent features of the financial system, the expansion of non-core activities has reduced their ability to perform their original function and generated additional systemic risk. Recent developments point to a renewed role, although a deeper reform of the NPL market will also be needed.